Upaya Pencegahan Stunting Melalui Pelatihan Pengolahan Nugget Ikan bagi Kelompok Nelayan Bintaro Ampenan NTB - Riezka Zuhriatika Rasyda; Siska Cicilia; Ahmad Alamsyah; Setyaning Pawestri; Nur Afni; Lingga Gita Dwikasari (PRIMA: Journal of Community Empowering and Services, 2026)
Stunting Prevention Efforts Through Fish Nugget Processing Training for Fishermen Groups in Bintaro Ampenan NTB. Stunting prevalence in West Nusa Tenggara Province (NTB) (24,6%) is still above the national rate (21,5%). One of the causes is the low diversity of food consumption from animal protein, including fish. The Bintaro Ampenan area is one of the marine fish production centers in NTB. Fishermen in this area still sell their catches fresh or minimally processed; if unsold, it quickly spoils and goes to waste due to their limited knowledge and skills regarding seafood processing. This community service activity aimed to empower these fishermen groups through the transfer of knowledge and appropriate technology about the processing of mackerel tuna nugget as an effort to prevent stunting. The activity used the method of training and hands-on practical assistance in processing fish nuggets. It was held on June 11, 2025, with 15 participants in Bintaro Subdistrict, Ampenan District, Mataram City, NTB Province. It ran smoothly, with participants showing high enthusiasm throughout the activity. The results showed an increase in the knowledge and skills of the fishing community regarding the processing of mackerel tuna nuggets. The increase in knowledge was reflected in the significant difference between the average pre-test score (59.00) and post-test score (85.00). The improvement in skills was reflected by the success of all participants (100%) in independently processing mackerel tuna nuggets. The Bintaro Ampenan fishermen group is expected to continue to produce fish nuggets independently and sustainably to optimize the potential of their area in an effort to help prevent stunting in their surrounding community.